Phenotypic Drug Resistance and Gene Mutation in Mycobacterium Tuberculosis with and without Diabetes: a Prospective Study - Yingmei ZHANG, Fei WANG, Xiaobing REN, Yuelian WANG, Jun CHEN, Ying HU, Xiaoqin HU, Wenge XU (Zhongguo quanke yixue, 2022)
Background It is difficult to prevent and control drug-resistant tuberculosis. The difficulty of containment will be increased if tuberculosis is accompanied with diabetes. There is no clear conclusion on whether diabetes affects phenotypic drug resistance in tuberculosis. Objective To assess the association of diabetes with phenotypic drug resistance and gene mutation in mycobacterium tuberculosis. Methods A total of 357 culture-positive tuberculosis patients were recruited from the People's Hospital of Jianyang City from 2018 to 2020, including 216 with pulmonary tuberculosis (PTB) , and 141 with PTB and diabetes (DM-PTB) . Early morning sputum samples were tested with drug sensitivity test for mycobacterium tuberculosis. And 62 patients in the PTB group and 61 patients in the DM-PTB group were chosen to undergo test for mutations in drug resistance genes. Results The resistance rates to rifampicin, ethambutol and streptomycin were similar in the two groups (P>0.05) . Isoniazid resistance rate in DM-PTB group was significantly higher than that in PTB group (P<0.05) , while there were no significant intergroup differences in mono-drug resistance and ploy-drug resistance (P>0.05) . The multidrug resistance rate in DM-PTB group was higher than that of PTB group (P<0.05) . And there was no significant difference in rate of mutation at the gene loci between two groups (P>0.05) . Conclusion Diabetes will increase the rates of resistance to isoniazid and multidrugs in tuberculosis patients. So attention should be given to the screening of both tuberculosis and diabetes.